Effectiveness of the traffic management unit in the implementation of traffic rules and regulations in the City Proper District of Iloilo City - Mabunay-Jover, Liza Assumpta Escaalera; Barcellno-Ramos, Rolita Oberio; Bulos, Jonathan Pastor; Patricio, Roel Vencer (2001)
The purpose of this study was to measure the effectiveness of the Traffic Management Unit of iloilo city, and determine the causes of traffic problems. The data for this descriptive research were gathered through use of a questionnaire. The instruments asked for the respondents' opinions regarding the traffic problems and other related items needed for this study from the month of July to October, 2001. The participants of the present study were the 75 individuals residing at Iloilo City, who have one way or the other encountered traffic problems. The respondents were classified further according to respondent-related factors such as commuters, drivers and traffic enforcers. The frequency count, and rank were used as descriptive statistics, and Pearson's was used for the inferential statistics at 0.05 alpha level of significance. Results showed that, generally, the traffic management implementation of Iloilo City "Needs Improvement". The following were the causes of heavy traffic congestion in the City Proper, District of Iloilo City: increasing number of vehicles in the city, lack of discipline among drivers and commuters, narrow streets with no available space for its widening, lack of necessary training of some drivers in traffic rules and regulations, and presence of traffic obstructions. The measures that the Traffic Management Unit have done to solve the traffic congestion were the following: non-entry of provincial vehicles in the city streets, additional traffic enforcers, and rerouting scheme. The following are the indicators of effective traffic management in Iloilo City according to the commuters: proper use of the pedestrian lanes, usual time travel, most congested streets, time of the day that has heavy traffic, and presence of skywalk/overpass. Positive but not significant correlation was observed between the causes of the traffic congestion and the indicators of effectiveness of the traffic management.
Research Paper (PM 299-Public Management Research). -- [Iloilo City] : UPV, October 2001.